Using mechanisms of object-oriented programming for the unification of procedures of work with the monthly plan and for manufacture and shipment of the main production - N. P. Papkov; E. S. Onegina (Литьë и металлургия, 2019)
This article describes a version of the modernization of the software (SOFTWARE), which allows to create monthly production plans and shipping program for shops of the main production, which used some of the mechanisms of object-oriented programming. The result of this work was the unification of the same actions in the formation of monthly plans for different shops within the framework of this SOFTWARE, the use of the same objects in different parts of the SOFTWARE with rapid adaptation to specific requirements in this place, the possibility of using the obtained objects in the newly developed provision by various departments of development.